SISTEM TANGGUNG RENTENG SEBAGAI INSTRUMEN MANAJEMEN RISIKO PEMBIAYAAN MIKRO DI PT PERMODALAN NASIONAL MADANI (PNM) MEKAAR - Fitria Akibun; Iwan Lakoro; Moh Ramdhan Arif Kaluku; Regi Mokodongan; Fitriyanti Sahi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the effectiveness of the joint liability system in reducing non-performing loans and strengthening women’s economic empowerment within the PNM Mekaar program. The research employed a cross-sectional survey design involving 185 active respondents selected through purposive sampling. Data were analyzed using multiple linear regression and paired sample t-tests to examine the relationships among variables and changes in non-performing loan rates before and after the implementation of the system. The findings indicate that the joint liability system improved members’ repayment discipline by 87.6% and reduced the non-performing loan ratio from 8.3% to 2.1%. Social capital dimensions, including social networks, trust, and collective norms, were found to have a positive and significant effect on the system’s effectiveness (p < 0.05). In addition, financial literacy, mentoring quality, and consi stent supervision contributed to the program’s success. These findings highlight the importance of social capital in supporting microfinance sustainability and enhancing women’s economic empowerment.